RIVALITAS PADA PILKADA SERENTAK TAHUN 2015 DI KABUPATEN MAJENE - asriani Asraini; Andi Nur Fiqhi Utami; Zainuddin Losi (Jurnal Arajang, 2019)
The research aimed to determine and analyze the competition of candidate pairs and the effect of decisive elite on the candidate pairs in obtaining votes in the 2015 Regional Head Election in Majene Regency. The research was a qualitative study with descriptive analysis type conducted in Majene Regency. The informants were determined using purposive sampling method. The data were obtained through in-depth interview and library study. The data were analyzed using rivalry concept, capital strength approach, decisive elite concept, and exchange theory. The results of the research indicate that each candidate pairs competes with each other by maximizing the owned capital strength. Fahmi Massiara – Lukman victory is obtained because they are able to accumulate modalities, i.e. symbolic capital, financial capital and social capital. Rizal Sirajuddin – Mulyadi Bintaha pair is the second in obtaining votes by maximizing financial capital, and social capital. Arifin Nurdin – A. Irfan pair is the third as they do not maximizing financial capital, and the only have cultural capital. The involvement of elites in the 2015 Regional Head Election in Majene Regency has impact on candidate pairs in obtaining votes. The effects of decisive elites determine political position, title of nobility, and the owned financial ability. Decisive elites have interest in supporting the candidate pairs, i.e. to facilitate the vote in Majene in governor election of West Sulawesi.